2018
DOI: 10.1111/jhn.12532
|View full text |Cite
|
Sign up to set email alerts
|

Food addiction and associations with mental health symptoms: a systematic review with meta‐analysis

Abstract: A significant, positive relationship exists between food addiction and mental health symptoms, although the results of the present study highlight the complexity of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
165
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(211 citation statements)
references
References 82 publications
(253 reference statements)
22
165
0
6
Order By: Relevance
“…Our results suggest that another important psychopathological overlap between FA and EDs may be represented by body uneasiness. This is in accordance with previous findings showing that FA is frequently diagnosed (between 65% and 100%) in patients with a current diagnosis of BN and (between 41.5% and 72.2%) in patients with BED and clinical levels of binge eating (Burrows et al, ; Imperatori, Fabbricatore, et al, ). Therefore, as already hypothesized (Imperatori, Fabbricatore, et al, ; Treasure et al, ; Wiss & Brewerton, ), FA may be conceptualized as a trans‐nosographic construct in obese and overweight patients and in all patients with EDs, especially in those with BED and BN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest that another important psychopathological overlap between FA and EDs may be represented by body uneasiness. This is in accordance with previous findings showing that FA is frequently diagnosed (between 65% and 100%) in patients with a current diagnosis of BN and (between 41.5% and 72.2%) in patients with BED and clinical levels of binge eating (Burrows et al, ; Imperatori, Fabbricatore, et al, ). Therefore, as already hypothesized (Imperatori, Fabbricatore, et al, ; Treasure et al, ; Wiss & Brewerton, ), FA may be conceptualized as a trans‐nosographic construct in obese and overweight patients and in all patients with EDs, especially in those with BED and BN.…”
Section: Discussionsupporting
confidence: 93%
“…In the last decade, the construct of food addiction (FA) has gained increasing attention from researchers, and many controversies have emerged regarding both its conceptualization and nosological status (Burrows, Kay‐Lambkin, Pursey, Skinner, & Dayas, ). Although different definitions for FA exist and other terms have been used interchangeably with it (e.g., “eating addiction”; Hebebrand et al, ), the most common approach to conceptualize FA derives from the overlap of substance use disorder symptoms and diagnosis (e.g., loss of control over consumption, craving, withdrawal, and tolerance; American Psychiatric Association, , ).…”
Section: Introductionmentioning
confidence: 99%
“…This, to our knowledge, is the first study to examine FA in a study group of adults residing in India. The findings indicated that 32.5% of participants met the YFASdefined clinical level of FA, which is higher than observed in recent meta-analytic findings (16.2% to 19.9%) that compiled studies with samples predominantly from the United States (Burrows et al, 2018;Pursey et al, 2014). Our findings, however, were consistent with a recent study examining South Asian participants using similar research methodology, which cite a similar YFAS symptom mean in their sample (Meadows et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…and disordered eating behaviours, including emotional eating and binge eating (Burrows, Kay-Lambkin, Pursey, Skinner, & Dayas, 2018;Chao et al, 2017;de Vries & Meule, 2016;Gearhardt et al, 2009;Gearhardt et al, 2012;Gearhardt, Boswell, & White, 2014a;Pursey, Stanwell, Gearhardt, Collins, & Burrows, 2014;Schulte, Grilo, & Gearhardt, 2016;Wolz, Granero, & Fernandez-Aranda, 2017). FA appears more common in women, whereas studies examining the association of FA and racial/ethnic identity have been mixed (Burrows et al, 2018). Overall, the majority of studies examining FA have been conducted in the United States with relatively homogeneous participant groups (e.g., White women with obesity).…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study indicate a positive relationship between FA and depression in adolescents. Positive associations between FA and depression in adults (Burmeister et al, ; Burrows et al, ; Meadows et al, ) and adolescents (Ahmed et al, ) have been previously reported. A combined diagnosis of FA and depression was noted in 1.6% (18) of the adolescents surveyed, which is significantly less than previously reported in data from Egypt (10.4%; Ahmed et al, ).…”
Section: Discussionmentioning
confidence: 84%